PENYIDIKAN TERHADAP TINDAK PIDANA KORUPSI PENYALAHGUNAAN WEWENANG OLEH KEPALA DESA DALAM PEMBUATAN SURAT KETERANGAN TANAH DI WILAYAH HUKUM KEPOLISIAN RESOR PELALAWAN JIKA DIKAITKAN DENGAN BUDAYA HUKUM MASYARAKAT - Gunawan Hutagalung; Erdianto Effendi; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Letter shellfish Land is a government program that aims to facilitate citizens in the Land titling and registration is free, but today a lot going on corruption made accidentally (dolus) to seize the property of others. The purpose of this thesis, namely; First, the implementation of an investigation into the crime of abuse of authority of making statement on land in the jurisdiction of Police Palalawan; Second, obstacles to the implementation of criminal investigations of corruption misuse of authority-making statement on land in the resort Pelalawan police jurisdictions; Third, efforts are being made to overcome the obstacles in the implementation of criminal investigations of corruption misuse wewenanng manufacture certificate of land in the jurisdiction of Police Palalawan.This type of research is classified into types of juridical sociological, because in this study the authors directly conducting this research directly to conduct research on the locations or places studied in order to give a complete picture and clear about the issues examined, the study was conducted at the Police Pelalawan, while the population and the sample is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, technical data collectors in this study with interviews and literature study.From the results of research and discussion can be concluded that the First, implementation of criminal investigations in the jurisdiction of Police Palalawan not run well as it should. Second, obstacles to the implementation of criminal investigations of corruption misuse of authority-making statement on land in the jurisdiction of Police Palalawan is the difficulty in calling a witness, a limited number of police investigators and the lack of ability of the police in dealing with corruption cases of abuse of authority of making statement on land. Third, efforts made in overcoming obstacles in the implementation of criminal investigations of corruption misuse of authority-making statement on land is to coordinate with the witness, adding the number of personnel investigation team Police Palalawan and conduct specialized training for the implementation of the task of investigation of Police Palalawan against corruption cases wewenanng abuse pembutan statement on land.Keywords: Investigation-Crime-Abuse of Authority Making Certificate of Land